Potential of Modified Cassava Starch as a Tablet Binder in Direct Compression Method - Wira Noviana Suhery; Anita Lukman; Afriyanti Afriyanti (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2021)
Research on the potential of modified cassava starch as a binder for the direct compression method has been carried out. The use of modified cassava starch as a binder using six formulas with the drug model ibuprofen. Variations in the concentration of modified cassava starch were modified cassava starch 48 and modified cassava starch 72 were 15%, 17.5%, and 20%, respectively. The formula with a modified starch 72 concentration (15%) is the best formula that produced optimal tablets. The value of hardness was 5.3 kg/cm2, friability of 0.90%, and disintegration time of 2.06 minutes which are the main parameters of the binder